A new species of Chusquea sect. Serpentes (Poaceae: Bambusoideae: Bambuseae: Chusqueinae) endemic to Oaxaca, Mexico - Ruiz-Sanchez, Eduardo; Mejia-Saulés, Ma. Teresa; Clark, Lynn G. (Phytotaxa, 2022)
The most speciose bamboo genus worldwide is Chusquea with 195 described species, 24 of which occur in Mexico. Chusquea is classified into five subgenera, with two of them present in Mexico. Chusquea subg. Chusquea is classified into six sections, of which Chusquea sect. Serpentes has eight described species; one of them is present in Mexico. Forty-three years ago, S.D. Koch and P.A. Fryxell collected a vegetative Chusquea species from Suchixtepec, Oaxaca in the Sierra Madre del Sur with a circular central bud and the infravaginal branching pattern. The same unknown species was collected in 1993 by L.G. Clark, and again by E. Ruiz-Sanchez & L. Cervantes in 2013. Based on these collections and a morphological analysis, here we describe a new Chusquea species, C. kochii, in honor of the late agrostologist S.D. Koch. This species most closely resembles C. glauca. Here we present a geographical distribution map, illustrations, photographs, and a morphological comparison with C. glauca. Chusquea increases to a total of 196 described species, 25 of them present in Mexico, and sect. Serpentes now has nine species, two of them distributed in Mexico. The number of woody bamboo species native to Mexico increases to 58, with 41 of them, including C. kochii, endemic to Mexico.